1999
DOI: 10.1001/jama.282.18.1731
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Angiographic Characteristics of Exertion-Related Acute Myocardial Infarction

Abstract: These results show that exertion-related MIs occur in habitually inactive people with multiple cardiac risk factors. These individuals may benefit from modest exercise training and aggressive risk-factor modification before they perform vigorous physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
94
1
7

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(107 citation statements)
references
References 37 publications
5
94
1
7
Order By: Relevance
“…Giri et al reported that patients with an exertion-related MI were more likely to have risk factors including male sex, hyperlipidemia, hypertension and current cigarette smoking (59 % versus 37 % in non exertion-related MI) but in a population of which had known coronary artery disease and older than that of our study (Giri et al 1999). There were 28 cigarette smokers in a population of 42 patients in one study on unstable angina, SMI and SSD related to sport (Ciampricotti et al, 1990).…”
Section: Which Athletes and Which Sports?contrasting
confidence: 50%
“…Giri et al reported that patients with an exertion-related MI were more likely to have risk factors including male sex, hyperlipidemia, hypertension and current cigarette smoking (59 % versus 37 % in non exertion-related MI) but in a population of which had known coronary artery disease and older than that of our study (Giri et al 1999). There were 28 cigarette smokers in a population of 42 patients in one study on unstable angina, SMI and SSD related to sport (Ciampricotti et al, 1990).…”
Section: Which Athletes and Which Sports?contrasting
confidence: 50%
“…50 In some situations, regular physical activity actually reduces injury risk, as indicated by a recent consensus statement that physical activity is recommended to reduce the risk of fall injuries in older adults. 55 Vigorous physical activity acutely increases the risk of sudden cardiac death 56,57 and myocardial infarction 58,59 among individuals with both diagnosed and occult heart disease. A variety of congenital and acquired conditions such as hypertrophic cardiomyopathy, coronary artery anomalies, aortic stenosis, and cardiomyopathies are associated with sudden death during vigorous activity in children and young adults.…”
Section: Risks Of Physical Activitymentioning
confidence: 99%
“…56,57 Exercise also transiently increases the risk of acute myocardial infarction. 58,59 Approximately 5% to 10% of myocardial infarctions are associated with vigorous physical activity. The relative risk of both exercise-related myocardial infarction and sudden death is greatest in individuals who are the least physically active and who were performing unaccustomed vigorous physical activity.…”
Section: Risks Of Physical Activitymentioning
confidence: 99%
See 2 more Smart Citations